Controlling Antihypertensive and Antidiabetic Agents Planning with the ABC Critical Index Method: A Case Study in Denpasar City Hospitals - Yuliawati, Agustina Nila; Putri, Kadek Mita Wulandari; Wikayanti, Ni Putu Ayu Putri; Kurnianta, Putu Dian Marani (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Non-communicable diseases such as hypertension (HT) and diabetes mellitus (DM) are the main causes of morbidity and mortality in Indonesia, including Denpasar City. Both diseases require long-term therapy with adequate drug availability to achieve successful treatment. Therefore, effective and efficient management of pharmaceutical preparation planning is very important in hospitals. This study aims to analyze the control of pharmaceutical preparation planning for hypertension and DM therapy using the ABC Critical Index method in hospitals throughout Denpasar City. This research is a descriptive observational study with a case study design conducted at four selected hospitals in Denpasar through a cluster random sampling technique. Data collected includes usage value, investment, selling price, and critical value of antihypertensive and antidiabetic drugs during 2024. The data were then analyzed using the Pareto ABC method and the Critical Index using Microsoft Excel and presented descriptively. The results show that antihypertensive and antidiabetic drugs are generally in the Pareto group C based on use value and investment, with the majority of critical value categories being in category E (>70%). ABC Critical index analysis shows that most drugs are in the Cci group, but planning priorities are in the Aci group, which includes drugs in the ARB, CCB, loop diuretics, insulin, and metformin classes. These findings provide a basis for improving drug procurement management and more appropriate budget allocation in hospitals and suggest that ongoing monitoring can minimize drug shortages that disrupt health services.